Algorithmic Transparency in Information Systems: A Legal Necessity for the Protection of Fundamental Rights - Dragomir-Constantin, Florentina-Loredana (Acta Universitatis Danubius. Juridica, 2025)
Algorithmic transparency in critical information systems is an essential aspect in ensuring fair and responsible use of technologies that influence the daily lives of individuals. Algorithms are increasingly used in sensitive sectors such as finance, law, and healthcare, areas where automated decisions can have significant impacts on the fundamental rights of citizens. In the financial field, algorithms can influence access to credit, risk assessments, and investment management; in the legal system, they can determine sentences or risk assessments for defendants; and in the medical field, algorithms can decide on diagnoses or treatments for patients. Thus, algorithmic transparency becomes crucial for preventing errors and discrimination and protecting the fundamental rights of individuals. The purpose of this article is to analyse the importance of algorithmic transparency in these critical areas, identifying the main challenges and legal implications of their implementation. The methodology of the article is based on a multidisciplinary approach and proposes various regulatory and technological solutions, in order to protect the fundamental rights of individuals in the face of automated decisions.